Factor affecting final adult Height in children with central precocious puberty in Sulaimani governorate - Sharef, Khalid Hama Salih Hama; Hamawandi, Adnan Mohammed Hasan (Journal of Sulaimani Medical College, 2025)
Background: Central precocious puberty (CPP) can compromise final adult height (FAH) due to early epiphyseal closure. This study aimed to identify primary factors influencing FAH in children with CPP attending Endocrine department at Dr. Jamal Ahmad Pediatric Teaching Hospital in Sulaimani, Iraq. Methods: A retrospective, observational cohort study was conducted on 60 children diagnosed with CPP from January 2009 to December 2021. Data were collected from medical records, including demographic, clinical, laboratory, radiological findings, and treatment. Results: The study included 57 females and 3 males, with a mean age of at the time of data collection was 14.12 ± 1.74 years, while the mean chronological age at diagnosis of 7.52 ± 1.05 years. The mean height increased significantly from 131.61 ± 7.47 cm before treatment to 152.92 ± 4.62 cm after treatment. Bone age increased from 10.61 ± 1.67 to 14.29 ± 0.92 years. The factors affecting Final Adult Height, including: Height at diagnosis was a significant factor. Bone age advancement at diagnosis was also a factor affecting Final Adult Height. The treatment option was another factor affecting Final Adult Height. While the duration of treatment, BMI, result of investigation, and mid-parenteral height were statistically not significant. Conclusion: Effective treatment with GnRH agonists, with or without growth hormone and aromatase inhibitors, enables children with CPP to achieve final heights near or above target height. Genetic factors, including family history, significant positive impact on final height, while consanguinity shows a negative effect.
Keywords: Final adult height; central precocious puberty; Children; Sulaimani governorate